Household support for physical activity in adolescent girls recruited from lower SES neighborhoods - Rupp, Kristie; Taverno Ross, Sharon E.; Gary-Webb, Tiffany L.; Akiva, Thomas; Jakicic, John M. (Medicine & Science in Sports & Exercise, 2017)
0 citations (Crossref) [2023-10-31]
Keywords: dept.hms

Reducing sedentary behavior versus increasing moderate-to-vigorous intensity physical activity in older adults: a 12-week randomized, clinical trial - Gibbs, Bethany Barone; Brach, Jennifer S.; Byard, Tom; Creasy, Seth; Davis, Kelliann K.; McCoy, Stephanie; Peluso, Anna; Rogers, Renee J.; Rupp, Kristie; Jakicic, John M. (Journal of Aging and Health, 2016)
Objective: To compare the effects of behavioral interventions targeting decreased sedentary behavior versus increased moderate-to-vigorous intensity physical ac...
45 citations (Crossref) [2023-10-31] Publisher: SAGE PublicationsSage CA: Los Angeles, CA
Keywords: dept.hms